2021
DOI: 10.1108/jeee-05-2021-0197
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the internationalization of Chinese SMEs: thematic expansion, new impulses and potential avenues for future research

Abstract: Purpose Supplementing an earlier review paper on the internationalization of Chinese small- and medium-sized enterprises (SMEs) (ICS) that covers the period 1991–2012, the purpose of this paper is to examine how research on this topic has thematically expanded in recent years. Specifically, the authors aim to examine the literature between 2013 and 2020, highlight advancements and synthesize potential avenues for future research. Design/methodology/approach Based on the systematic literature review method (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…Many studies explored on entrepreneurship from various standpoints such as entrepreneurship and SME development (Abu Bakar et al, 2017;Kloepfer & Castrogiovanni, 2018;Melese, 2018;Hänle et al, 2022), entrepreneurship activities (Ngoma et al, 2021;Munyuki, T. and Jonah, 2022), venture capital and SME performance (Festel et al, 2015;Shava, 2018;Couto, 2020;(Kato & Germinah, 2022), observing it as a device for employment creation and poverty alleviation in emerging economies. However, studies on how VC investment can stimulate entrepreneurship development remains scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies explored on entrepreneurship from various standpoints such as entrepreneurship and SME development (Abu Bakar et al, 2017;Kloepfer & Castrogiovanni, 2018;Melese, 2018;Hänle et al, 2022), entrepreneurship activities (Ngoma et al, 2021;Munyuki, T. and Jonah, 2022), venture capital and SME performance (Festel et al, 2015;Shava, 2018;Couto, 2020;(Kato & Germinah, 2022), observing it as a device for employment creation and poverty alleviation in emerging economies. However, studies on how VC investment can stimulate entrepreneurship development remains scarce.…”
Section: Resultsmentioning
confidence: 99%
“…This study concluded that AMCs, GM, and CI are essential for IOI and IOE among Chinese internationalized traditional SMEs. Aghazadeh and Zandi (2023) claimed that literature didn’t present a great consensus on true born globals, instead, it has introduced the emergence of early and fast internationalization patterns such as “global new venture,”“born international” and “born again regional.” In their systematic review on the internationalization of Chinese SMEs, Hänle et al (2022) found that a growing internationalization research stream starting from 2013 and onward has focused on investigating the global expansion of SMEs with emphasis on the role of firm-level characteristics, sources of internal capabilities and social networks. Our study reported that the internal capabilities possessed by SMEs’ managers: AMCs, GM, and CI were closely related to effective identification and exploitation of international opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…We approach our study by deploying a concept-centric systematic literature review as recommended by some scholars (Levy and Ellis, 2006; Webster and Watson, 2002; Rowe, 2014; Paré et al , 2017; Okoli, 2015; Schryen, 2013). A systematic literature review provides detailed steps, identifying, analysing, evaluating and interpreting prior relevant studies in a given area of interest (Castro and Zermeño, 2020; Chan and Mustafa, 2020; Ahmad and Bajwa, 2021; Aldairany et al , 2018; Aljuwaiber, 2020; Hänle et al , 2021; Khan et al , 2022; Sharma, 2018; Santisteban and Mauricio, 2017; Claire et al , 2019; Yamamura and Lassalle, 2022; Bansal et al , 2020). Consequently, it provides a rigorous process, free of biases and the credible outcome needed by researchers as a foundation for advancing knowledge (Webster and Watson, 2002; Okoli, 2015; Mahdavi, 2011).…”
Section: Systematic Literature Review Methodologymentioning
confidence: 99%